Intrauterine Insemination Success Rates Between Patients TSH Level of 2.5 mIU/L and 2.5-4.5 mIU/L - Gizem Berfin Uluutku; Basak Ergin; İbrahim Kale; Rahime Nida Bayık (Tropical Health and Medical Research, 2021)
The aim of this study to assess whether there is a need to decrease the TSH level below 2.5 mIU/L in unexplainable infertility patients who were undergoing intrauterine insemination and determining the difference between patients with a TSH level of 2.5 mIU / L and patients with a TSH level of 2.5-4.5 mIU/L in terms of the success of intrauterine insemination. This study conduct via cross-sectional examinations of the 272 patients who applied to Ümraniye Training and Research Hospital infertility outpatient clinic between 01.06.2017-01.10.2019, who underwent intrauterine insemination with the diagnosis of unexplained infertility. Results research the mean age of the cases participating in our study is 31.65 ± 5.28, and the mean BMI measured as 24.17 ± 4.30 kg / m2. TSH values range from 0.3 to 5.2, with an average of 1.84 ± 0.93; while TSH value of 174 cases (77.3%) is below 2.5 mIU/L, TSH value of 51 cases (22.7%) is between 2.5-4.5mIU/L. Within the control group with TSH <2.5 mIU/L, the cycle was canceled in 13 cases (7.5%), pregnancy did not occur in 143 cases (82.2%). While ongoing pregnancy was achieved in 17 cases (9.8%), clinical pregnancy was achieved in 1 case (0,6%). Also, within the study group with a TSH value of 2.5-4.5 mIU/L, cycles were canceled in 7 cases (13.7%), pregnancy did not occur in 40 cases (78.4%), and ongoing pregnancy was achieved in 4 patients (7.8%). There was no statistically significant difference in terms of intrauterine insemination success between the control group with TSH <2.5 mIU / L and the study group with TSH 2.5-4.5 mIU/L. Widespread randomized controlled prospective studies need to determine the optimal TSH threshold value before TSH treatment of the women receiving infertility treatment.